(untitled) (Andamios, Revista de Investigación Social, 2025)
Highly conflictive, spontaneous, and self-organized events have occurred around the world in recent years, bringing together a heterogeneous multitude of people, generating collective action and constituting a landmark where they occur. This article reflects on these events as processes of community building, taking the October 2019 outbreak in Chile as a reference, seeking to explore the articulation, unity, and identity they awaken, the senses of political action they activate, and the paradox of the very possibility of community in the coexistence of the single and the multiple. In this way, the aim is to contribute to the study of the multiple dimensions and edges of this type of event.